Republic of Latvia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper assesses whether Latvia's strategy to enter ERM2 and adopt the euro is appropriate. The paper examines the possibility of an exchange rate misalignment from various perspectives. It considers different notions of the real effective exchange rate and competitiveness; deviations of the exchange rate from statistically defined equilibrium concepts; and the possibility that central bank foreign exchange interventions have maintained the exchange rate artificially away from equilibrium. The paper finds little evidence of a major misalignment. The paper also analyzes modeling inflation in Latvia.